Production of resistant starch type III and IV and their in vivo characterisation using balb/c mice model - Mohd Zaman, Siti Aisyah (2015)
Sago is an important agricultural commodity for Sarawak. The potential of sago is highlighted in the Malaysia’s 11th plan as part of the poverty eradication programme. Sago starch indigestibility provides a new perspective of sago utilisation as a prebiotic. The indigestible portion of starch is termed as resistant starch (RS). In the present study, RS type III and IV were produced through retrogradation and chemical modifications respectively. Retrogradation was done on different starch paste concentration of 10, 18 and 30%. The resultant RS type III was analysed for solubility, swelling power, amylose and RS content. Resistant starch type IV was produced through hydroxypropylation, acetylation, cross-linking and double modification combining acetylation and crosslinking. The resultant RS was subjected to the same analysis as RS type III. Native sago starch, retrograded starch at 18% initial starch paste concentration, 2% acetylated starch and double modified starch combining 1.5% cross-linking and 2% acetylation were further analysed for prebiotic evaluation through in vivo study using BALB/c mice model. All RS was supplemented into a standardised AIN93-M feed formulation. Feeding treatment was conducted for 4 weeks. The daily feed intake and body weight were recorded. Faeces samples were collected on the eighth day and on the final three consecutive days of feeding treatment. All faeces samples were subjected to short chain fatty acid analysis using highperformance liquid chromatography. All starch modifications showed an increase in solubility and swelling power. Native sago showed a high content of RS at 69%. Retrograded starch showed a significantly low amylose and RS content than native starch (P < 0.05). Only 1.5 and 2% acetylation, as well as double modification of 1.5% crosslinking and 2% acetylation showed an increase in RS content than native sago starch. Cross-linking and double modified starch showed an increase in amylose content at all level of modification. Mice fed diet supplemented with RS type III and acetylation showed a better overall growth performance with an increase of body weight with a decrease in feed intake. Mice fed diet supplemented with double modified and native sago starch showed a weight loss with a decrease in feed intake. This pattern supported satiety properties. Short chain fatty acid analysis showed the highest lactate production in mice fed diet supplemented with double modified starch at 43.57%. The highest propionate concentration was shown in mice fed diet supplemented with RS type III and double modified starch at 10.4%. The results showed that double modified sago starch has the potential as a prebiotic candidate ingredient. The weight reduction potential shown in a diet supplemented with double modified starch could also be further implemented in a weight management diet.